132k views
0 votes
Which of the following expressions are equivalent?

A. –3(3x + 5) and –9x + 5
B. 7(6x – 1) and 42x – 7
C. –6(4x – 3) and –6x
D. 5(2x + 3y) and 25xy

1 Answer

7 votes

Answer:

B. 7(6x – 1) and 42x – 7 is equivalent

Explanation:

A. –3(3x + 5) and –9x + 5

=–3(3x + 5)=-9x-15 not equivalent

B. 7(6x – 1) and 42x – 7

7(6x – 1)=42x-7 equivalent

C. –6(4x – 3) and –6x

=–6(4x – 3)=-24+18 not equivalent

D. 5(2x + 3y) and 25xy

=5(2x + 3y)=10x+15y not equivalent.

User Abhishek Pansotra
by
4.6k points